- #1

manenbu

- 103

- 0

## Homework Statement

y'' -6y' + 9y = f(t)

f(t)=

0, 0<t<1

1, 1<t<3

0, t>3

## Homework Equations

## The Attempt at a Solution

Turning it to heaviside functions I get:

y'' -6y' + 9y = u

_{1}- u

_{3}

and I solve.

in the answers it should be:

y(t) = 2te

^{t}+ u

_{1}(1/9 - 1/9e

^{3(t-1)}+ 1/3(t-1)e

^{3(t-1)}).

where did u

_{3}go in the answers? why doesn't it appear? the u

_{1}I can get just like that, but I can't seem to figure out where the u

_{3}went and why there is a 2te

^{t}in there.